Magnetic fields and thermodynamical conditions in the M6.4/3N solar flare on July 19, 2000 - Kurochka, E.V.; Lozitsky, V.G. (Кинематика и физика небесных тел, 2005)
We present the semi-empirical model of a powerful solar flare on July 19, 2000 based on spectral observations in the Fe I, Fe II, Cr I, and Ti II lines. Our calculations show the existence of a very narrow (≤ 100 km) and sharp magnetic field peak at photospheric level (log τ5 ≈ −2). It is possible that this peculiarity is indicative of the local magnetic field amplification due to specific process during the flare. Yet another interesting detail of the model is two discrete hot flare layers related to the middle photosphere and temperature minimum zone.